Be a Mom, a Web-Based Intervention to Prevent Postpartum Depression: Results From a Pilot Randomized Controlled Trial. Issue 4 (July 2020) - Fonseca, Ana; Alves, Stephanie; Monteiro, Fabiana; Gorayeb, Ricardo; Canavarro, Maria Cristina
Highlights: Be a Mom is a self-guided web-based intervention to prevent PPD. A higher number of women in the Be a Mom group improved over time. 41.8% of women who registered for Be a Mom completed the program. Most women showed good indicators of the program's acceptability. Be a Mom showed efficacy as a selective/indicative intervention for PPD. Abstract: Be a Mom is a self-guided web-based intervention, grounded in cognitive behavioral therapy, delivered to postpartum women to prevent persistent postpartum depression [PPD] symptoms. We aimed to evaluate Be a Mom in terms of its preliminary efficacy, feasibility, and acceptability. A pilot randomized, two-arm controlled trial was conducted. Eligible women (presenting PPD risk-factors and/or early-onset PPD symptoms) were enrolled in the study and were randomly assigned to the intervention (Be a Mom) or to the waiting-list control group. Participants in both groups completed baseline (T1) and postintervention (T2) assessments. The 194 women presenting risk factors/early-onset PPD symptoms were allocated to the intervention ( n  = 98) or to the control ( n  = 96) group. A significant Time × Group interaction effect was found for both depressive and anxiety symptoms, with women in the intervention group presenting a larger decrease in symptoms from T1 to T2 ( p  < .05). Less than half of the women (41.8%) completed Be a Mom. Most women (71.4%) would use Be a Mom again if needed. Results provide preliminary evidence of the Be a Mom's efficacy, acceptability and feasibility, although further research is needed to establish Be a Mom as a selective/indicative preventive intervention for persistent PPD.